A novel phenolic propanediamine moiety-based lung-targeting therapy for asthma - Jianbo Li; Yang Yang; Didi Wan; Youmei Peng; Jinjie Zhang (Taylor & Francis Group, 2018)
Asthma is one of the most prevalent chronic inflammatory diseases of lung. Current asthma therapy using inhaled corticosteroid often results in undesired treatment outcome due to poor compliance and drugs' lack of tissue specificity. N,N,N'-trimethyl-N'-(2-hydroxyl-3-methyl-5-123Iiodobenzyl)-1,3-propanediamine (HIPD), a phenolic propanediamine derivative, has been used as an imaging agent for localized pulmonary diseases. Inspired by this, N,N,N'-trimethyl-N'-(4-hydroxyl-benzyl)-1,3-propanediamine (TPD), a new HIPD analog, was proposed as a lung-targeting ligand and covalently conjugated to an anti-inflammatory compound Rhein for asthma therapy. Cellular uptake efficiency of TPD-Rhein by A549 cells was significantly enhanced compared with Rhein. The enhanced cellular uptake was mainly mediated by organic cation transporters (OCTs) in an active manner, showing concentration- and energy-dependent. After systemic administration in rats, TPD-Rhein specifically distributed to lungs, displaying the highest Cmax and AUC0−t values of all tested tissues and resulting in a 13-fold increase in Cmax and a 103-fold increase in AUC0−t for lung compared with Rhein. Also, TPD-Rhein remarkably decreased serum histamine levels, serum IL-5 levels as well as bronchoalveolar lavage fluid IL-5 levels in lungs of asthmatic rats challenged by ovalbumin (OVA). Accordingly, histological examinations demonstrated that TPD-Rhein attenuated lung inflammation in rats, with no apparent toxicity against major organs. Together, phenolic propanediamine-based lung-targeting approach represents an efficient and safe strategy for asthma therapy.